问题 解答题
用你认为简便的方法计算.
5
8
+(
22
27
-
5
8
8
9
-
1
6
+
2
3
6
7
+
1
6
-(
3
8
-
1
7
1-
1
14
-
2
7
1
4
+
2
5
)×20
25÷2
1
2
÷12.
答案

5
8
+(
22
27
-
5
8
),

=

5
8
-
5
8
+
22
27

=

22
27

8
9
-
1
6
+
2
3

=

8
9
+
2
3
-
1
6

=

4
3
-
1
6

=

7
6

6
7
+
1
6
-(
3
8
-
1
7
),

=

6
7
+
1
6
-
3
8
+
1
7

=(

6
7
+
1
7
+
1
6
-
3
8

=1+

1
6
-
3
8

=

19
24

④1-

1
14
-
2
7

=1-(

1
14
+
2
7
),

=1-

5
14

=

9
14

⑤(

1
4
+
2
5
)×20,

=

1
4
×20+
2
5
×20,

=5+8,

=13;

⑥25÷2

1
2
÷12,

=25×

2
5
×
1
12

=

5
6

单项选择题
问答题 简答题